Supplementing Coursebooks--How, Why, and to What Effect: A Case Study - Harper, John (Journal of English Language Teaching and Linguistics, 2019)
This article reports on a case study of one instructor?s use of supplementary materials in an English as a Foreign Language course in China. Starting with the notion that no coursebook can be perfect and that supplementary materials therefore should form part of an English course, the study employed qualitative research methods to analyze the types of supplements used, the instructor?s rationale behind his use of the supplements, and the students? interpretations of the supplements. Class observations, semi-structured interviews with the teacher, and focus-group discussions with students allowed for the triangulation of data. Findings indicated that the instructor provided a variety of types of supplementary materials in order to cater to different learner needs (specifically, affective needs, language-learning needs, course-content needs). While findings also indicated that learners generally appreciated the instructor?s use of supplementary materials, significant mismatches between instructor goals and learner interpretations suggested that the purpose of the supplements was not always clearly defined. The article addresses these mismatches and provides suggestions for their future avoidance.